2020
DOI: 10.4018/978-1-7998-0426-0.ch002
|View full text |Cite
|
Sign up to set email alerts
|

The Student Experience of Video-Enhanced Learning, Assessment, and Feedback

Abstract: Evaluating the impact on the student experience of the integrated model of video-enhanced learning, assessment, and feedback discussed in the previous chapter, qualitative data collection employed anonymous online questionnaires, semi-structured interviews, and dialogic interviewing techniques, drawing on summative results data to inform methodological triangulation of the findings. Data analysis combined thematic analysis, constant comparison, and direct interpretation within a grounded theory framework. Illu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Qualitative data collection employed anonymous online questionnaires, semi-structured interviews and dialogic interviewing techniques, drawing on summative results data to inform methodological triangulation of the findings. Data analysis combined thematic analysis, constant comparison and direct interpretation within a grounded theory framework (Glaser & Strauss, 1967), and illustrative cases presented the findings as thick descriptions of the influence of video-based interventions on the experience of six purposively and representatively selected participants (McDowell, 2019a). The investigation revealed that an integrated model of asynchronous video-enhanced learning, assessment and feedback can promote increased reflexivity, enhance learner autonomy and encourage meta-cognitive self-awareness, while affording greater inclusivity for students affected by dyslexia or Asperger's Syndrome (McDowell, 2019b).…”
Section: Investigating the Impact Of Integrated Video-enhanced Learnimentioning
confidence: 99%
“…Qualitative data collection employed anonymous online questionnaires, semi-structured interviews and dialogic interviewing techniques, drawing on summative results data to inform methodological triangulation of the findings. Data analysis combined thematic analysis, constant comparison and direct interpretation within a grounded theory framework (Glaser & Strauss, 1967), and illustrative cases presented the findings as thick descriptions of the influence of video-based interventions on the experience of six purposively and representatively selected participants (McDowell, 2019a). The investigation revealed that an integrated model of asynchronous video-enhanced learning, assessment and feedback can promote increased reflexivity, enhance learner autonomy and encourage meta-cognitive self-awareness, while affording greater inclusivity for students affected by dyslexia or Asperger's Syndrome (McDowell, 2019b).…”
Section: Investigating the Impact Of Integrated Video-enhanced Learnimentioning
confidence: 99%